2017
DOI: 10.1016/j.biopsych.2016.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Brain Imaging Reveals Structural Differences in Alzheimer’s Disease Polygenic Risk Carriers: A Study in Healthy Young Adults

Abstract: BackgroundRecent genome-wide association studies have identified genetic loci that jointly make a considerable contribution to risk of developing Alzheimer’s disease (AD). Because neuropathological features of AD can be present several decades before disease onset, we investigated whether effects of polygenic risk are detectable by neuroimaging in young adults. We hypothesized that higher polygenic risk scores (PRSs) for AD would be associated with reduced volume of the hippocampus and other limbic and paralim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(116 citation statements)
references
References 75 publications
(97 reference statements)
12
102
2
Order By: Relevance
“…While this A/T/N framework has emerged in studies of preclinical disease, it has not been integrated into PRS for AD despite the availability of GWAS summary statistics for autopsy and in vivo measures of A/T/N [20,21]. Indeed, a previous study suggested that shared genetic drivers for hippocampal volume (a marker of neurodegeneration) and AD may exist [22]. Thus, integrating the common and independent genetic drivers of clinical AD and A/T/N could produce models with higher predictive capacity for cognitive decline in late life.…”
Section: Introductionmentioning
confidence: 99%
“…While this A/T/N framework has emerged in studies of preclinical disease, it has not been integrated into PRS for AD despite the availability of GWAS summary statistics for autopsy and in vivo measures of A/T/N [20,21]. Indeed, a previous study suggested that shared genetic drivers for hippocampal volume (a marker of neurodegeneration) and AD may exist [22]. Thus, integrating the common and independent genetic drivers of clinical AD and A/T/N could produce models with higher predictive capacity for cognitive decline in late life.…”
Section: Introductionmentioning
confidence: 99%
“…The AD PGRS has been found to be associated with the risk of familial late-onset AD (Tosto et al, 2017), accelerated progression from mild cognitive impairment (MCI) to AD (Rodriguez-Rodriguez et al, 2013), cognitive scores (Verhaaren et al, 2013), and neuroimaging measures, including total brain volume (Chauhan et al, 2015), hippocampal volume (Chauhan et al, 2015;Foley et al, 2017;Lupton et al, 2016;Mormino et al, 2016), the cortical thickness in AD-vulnerable regions (Sabuncu et al, 2012), and the fractional anisotropy of the right cingulum (Foley et al, 2017). These studies, especially the neuroimaging studies, help to elucidate the mechanisms of the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 genetic contribution to AD risk.…”
mentioning
confidence: 99%
“…Here, these prior observations are expanded on to show that these alterations are also present in early life process. Together, accumulating evidence now suggests that both common and rare variations that confer risk for AD may converge on pathophysiological mechanisms such as alterations in subcortical volumetry in early life [6,8]. Furthermore, there was a negative association between the TREM2 risk allele and volume of putamen.…”
Section: Discussionmentioning
confidence: 99%